Diversity-productivity relationships of savanna ecosystems in the Cerrado-Pantanal transition of southern Mato Grosso, Brazil - Vourlitis, George L.; Pinto, Osvaldo Borges; Dalmagro, Higo J.; Arruda, Paulo H.; de Almeida Lobo, Francisco (Frontiers in Forests and Global Change, 2024)
Productivity and ecosystem carbon (C) storage are often positively associated with species and/or structural diversity; however, positive relationships in tropical forests and woodlands are not universal and the strength of this relationship may be affected by climate. Diversity-productivity relationships were evaluated in upland and seasonally flooded savanna (Cerrado) of the Cuiaba Basin and Northern Pantanal in southern Mato Grosso, Brazil. Data on wood C increment, tree species composition, and alpha diversity were measured over a 10-year period in nine communities located in the Cerrado-Pantanal transition zone. Communities were composed of a wide spectrum of tropical savanna physiognomies, including mixed grassland (campo sujo), typical wooded savanna (stricto sensu), dense wooded savanna (cerrado denso), seasonal forest (mata seca and mata ciliar), and riparian forest (mata de galeria). We hypothesized that tree species richness and diversity would increase from grassland to forest. We further hypothesized that there would be a positive relationship between woody C storage and diversity, but the strength of this relationship would be higher in wet years and wetter environments, such as the Pantanal, due to an increase in water availability. We found that tree species richness and diversity did not increase from mixed grasslands to forests, as mixed grasslands and riparian forests had similarly low levels of tree species richness and diversity compared to the other physiognomies. However, the rate of annual aboveground wood C increment was positively related to species richness and alpha diversity, and the positive relationship was primarily observed during wet years when the annual precipitation was at, or above, the long-term average for the region. Presumably, the impact of structural and species diversity on productivity declines during dry years when water availability becomes a more important control on stem C increment for tree species in the Cerrado-Pantanal transition. These data suggest that maintenance of diversity in these Cerrado woodlands and forests is important for maximizing aboveground C gain. However, climate change, which is causing warming and drying for the region, may limit the importance of diversity on wood C storage.